Resituating Funds of Identity Within Contemporary Interpretations of Perezhivanie - Poole, Adam; Huang, Jingyi (Mind, culture and activity, 2018)
There is still a tendency for researchers and teachers using a Funds of Identity approach for social justice purposes to exclude negative emotions and experiences from the classroom. This article addresses this issue by situating Funds of Identity within contemporary interpretations of perezhivanie to theorize what we call existential funds of identity, which we present as an enrichment of the Funds of Identity approach. The findings from a case study of Valerie, a 16-year-old Chinese high school student, suggest that both positive and negative emotions and experiences can be accommodated in the classroom through the use of new technology, which can also help to bridge the gap between home and school.